Between Metaphysics and Phenomenology: Metaxology in Simone Weil, Maurice Blondel, and William Desmond - Gabellieri, Emmanuel (Irish theological quarterly, 2024)
In this article, I argue that at the heart of the crisis of metaphysics and ecology is a separation of being and phenomenon, which invites the rediscovery of the analogical mediation of the natural and the supernatural. In part one, I survey the separated philosophy implied in a post-Husserlian methodological dilemma between prioritizing either phenomenology or metaphysics to suggest an alternative approach through the writings of Simone Weil and Maurice Blondel. In part two, I connect the approach of the Irish philosopher William Desmond to this intellectual project that holds open a vital dialogue between philosophy and theology.